Relationship between orthostatic blood pressure changes and intensive blood pressure management in patients with hypertension. Issue 2 (25th August 2022) - Pei, Junyu; Zhang, Hao; Li, Yanan; Yan, Jiafu; Zheng, Keyang; Wang, Xiaopu; Zheng, Xi-Long; Hu, Xinqun
Abstract : Introduction: The Systolic Blood Pressure Intervention Trial (SPRINT) demonstrated that closely controlling blood pressure (BP) could decrease cardiovascular outcome risk without increasing the orthostatic hypotension rate. We aimed to evaluate the association between baseline orthostatic BP change and major adverse cardiovascular event (MACE) occurrence. Methods: We conducted a post hoc analysis using SPRINT data including 9329 patients with hypertension. The SPRINT trial was a two-arm, multicentre, randomised clinical trial designed to test whether an intensive treatment aimed at reducing systolic BP (SBP) to <120 mm Hg would reduce cardiovascular disease risk. Orthostatic BP change was defined as baseline standing systolic BP (SBP)−baseline mean seated SBP, or diastolic BP (DBP)−baseline mean seated DBP. Results: We found a U-shaped relationship between orthostatic BP changes and MACE occurrence. All lowest risk points were around 0 mm Hg. On the left side of the inflection point, MACE risk decreased with orthostatic BP change decrease (HR=0.99, 95% CI (0.98 to 1.00), p=0.04, SBP change) (HR=0.97, 95% CI (0.95 to 0.99), p<0.01, DBP change); on the right side, MACE risk increased with orthostatic BP change increase (HR=1.02, 95% CI (1.01 to 1.06), p<0.01, SBP change) (HR=1.01, 95% CI (1.00 to 1.03), p=0.16, DBP change). There was no significant interaction effect between orthostatic SBP (p for interaction=0.37) or DBP changes (p for interaction=0.33) and intensive BP management. Conclusions: Orthostatic DBP increase and SBP decrease were associated with an increased MACE risk. The benefits of intensive BP management were also consistent across different orthostatic BP change ranges.